2006
DOI: 10.1080/08860220600599084
|View full text |Cite
|
Sign up to set email alerts
|

ACE Gene Polymorphism in Turkish Children with Nephrotic Syndrome

Abstract: Since 1990, the role of angiotensin converting enzyme (ACE) gene polymorphism in various renal and cardiac diseases is still debated. This study comprised 71 pediatric patients with nephrotic syndrome, 47 males (66%) and 24 females (34%) with a mean age of 57.4 +/- 37.6 months, and a control group of 83 healthy males (59%) and 57 healthy females (41%) with a mean age of 505 +/- 160.5 months. The distribution of the ACE genotype in the control group was II, 11%; ID, 53%; and DD, 36%, and the nephrotic syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…However, two investigations [6] [25] were performed in Caucasians and Africans respectively, which were excluded from our meta-analysis. Finally, five studies [4], [8], [26], [27], [28] were recruited into our investigation for the relationship between ACE I/D gene polymorphism and SRNS susceptibility (Table 1). Interestingly, all the recruited investigations were performed in children and those studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two investigations [6] [25] were performed in Caucasians and Africans respectively, which were excluded from our meta-analysis. Finally, five studies [4], [8], [26], [27], [28] were recruited into our investigation for the relationship between ACE I/D gene polymorphism and SRNS susceptibility (Table 1). Interestingly, all the recruited investigations were performed in children and those studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one report [6] was conducted in Caucasians and two [25], [30] were in Africans, and these were excluded from our investigation for the relationship between ACE I/D gene polymorphism and SSNS risk. Seven studies [4], [8], [14], [26], [27], [28], [31] were identified for the analysis of the association between ACE I/D gene polymorphism and SSNS susceptibility in our final review (Table 2). Interestingly, all the included studies were performed in children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of ACE gene polymorphism to the incidence or clinical severity of INS varies among different studies [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. DD genotype or D allele were found to be associated with the overall susceptibility to INS, as well as susceptibility to MCD and FSGS in Asian children [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The increased Ang II plays deleterious effects on renal hemodynamics and increases the expression of some growth factors that can take part in the onset and progression of various renal diseases [3,4,5,6,7,8]. The relationship between ACE gene I/D polymorphism and INS in children has been investigated with conflicting results [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. The majority of investigations have been performed in Asian populations, with only scarce information from Europe and other parts of the world.…”
Section: Introductionmentioning
confidence: 99%